EFEKTIVITAS PROGRAM E-KINERJA DALAM LAYANAN PENYELENGGARA PEMERINTAHAN BERBASIS ELEKTRONIK DI KELURAHAN PUCANG KECAMATAN SIDOARJO KABUPATEN SIDOARJO - Nafisa Kamelia Al Hisyam; Isna Fitria Agustina (Journal Publicuho, 2025)
The purpose of this study is to describe the effectiveness of the e-Performance program in electronic-based government service providers in Pucang village, Sidoarjo District. The study uses a descriptive, qualitative research type and data collection through observation, interviews, and documentation, with the intention of being able to objectively describe the facts and phenomena that are the research problems. The results of the study based on the theory of effectiveness, according to Duncan in Steer s show that the e-Performance program is already effective because it has attempted training on the e-Performance application. However, there are still some who do not understand how to apply it because of the training that is not intense, and the distribution of uneven information.